2011
DOI: 10.1143/jjap.50.07he03
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Microstructural Deformation Behavior in Metals Caused by Cavitation Impact

Abstract: To clarify the erosion mechanism of cavitation, we pay attention to the internal changes in grains caused by cavitation impact. The vibratory cavitation test based on ASTM G32 was carried out and the cross section of directly under the eroded surface of a specimen was observed using the electron backscattering diffraction (EBSD) technique. The situations of grain boundaries and the changes in the crystal orientations of grains in aluminum, copper, and steel were analyzed. As a result, the following observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Ultrasonic cavitation, as a nonlinear acoustic phenomenon, involves the dynamic processes of expansion, oscillation, compression, and collapse in a liquid medium [6][7][8]. Studies have reported that ultrasonic vibration helps to eliminate bubbles in the electroplating solution and prevents interference from hydrogen bubbles during the coating formation process, thereby increasing the density and crystallinity of the coating, reducing the formation of pores, and promoting denser coating formation, resulting in submicron-level grain refinement on the eroded surface [9,10]. Liu et al [11] found that ultrasonic cavitation is suitable for processing the surface microstructure of workpieces to improve processing for enhanced bonding strength.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic cavitation, as a nonlinear acoustic phenomenon, involves the dynamic processes of expansion, oscillation, compression, and collapse in a liquid medium [6][7][8]. Studies have reported that ultrasonic vibration helps to eliminate bubbles in the electroplating solution and prevents interference from hydrogen bubbles during the coating formation process, thereby increasing the density and crystallinity of the coating, reducing the formation of pores, and promoting denser coating formation, resulting in submicron-level grain refinement on the eroded surface [9,10]. Liu et al [11] found that ultrasonic cavitation is suitable for processing the surface microstructure of workpieces to improve processing for enhanced bonding strength.…”
Section: Introductionmentioning
confidence: 99%